Measurement of the risk factors of food security during flood disaster at Bera, Pahang / Nurdayana Hassan - Hassan, Nurdayana (2010)
Flood is one of disaster that can cause damage and destruction. During flood, people can easily get food bome illness due to the food storage and supply. This condition deals with the food security. However, limited information about the risk factors of food security during flood disaster. Therefore, this study aims to identify and measured the risk factors of food safety during flood disasters and its relation with the nutritional status. A cross sectional study was conducted using District and Community Questionnaire among the villagers that affected by flood. There were hundred respondents from 13 villages of Bera district were chosen as it located along the Pahang basin area. Data were obtained through self-administered questionnaire and anthropometric data. Based on the data obtained, it reported that the risk factors of food security during flood were in term of foods and beverages, living place and clothing, water access, electricity and transportation with frequency of 96%, 77%, 74%, 50% and 43% respectively. The association of risk factors with sick persons and meal intakes during floods give result of no significance at all with the other factors however, shows the significance at the factors of living place and clothing with meals intake, which the P= 0.027 (P<0.05). Findings on the relationship of live impacts with nutritional status shows that the Chi-square test are not significance as the P value was P< 0.352. Flood disasters can risk the livelihood due to all the factors.